Respuesta :

Hello and Good Morning/Afternoon

Let's take this problem step-by-step:

First step

⇒ consider the fact cotθ = 1 / (tanθ)

 [tex]\frac{1+tanx}{1+cotx} =\frac{1+tanx}{1+\frac{1}{tanx} }[/tex]

Second step

⇒ form a common denominator for the fraction in the 'denominator'

[tex]\frac{1+tanx}{1+\frac{1}{tanx} } =\frac{1+tanx}{\frac{tanx+1}{tanx} }[/tex]

Let's flip over the fraction on the denominator

[tex]\frac{1+tanx}{\frac{tanx+1}{tanx} } =(1+tanx) * \frac{tanx}{1+tanx} =tanx[/tex]

And there you go, you have proved the statement by following these steps!

 *note, I used 'x' because the equation creator didn't have 'θ' symbol

Hope that helps!

#LearnwithBrainly